Monitoring of Soil-borne Parasites in Various Children’s Play Facilities in the Republic of Korea (2016-2021) - 오영환 (The Graduate School, Ajou University, 2024)
Monitoring of Soil-borne Parasites in Various Children’s Play Facilities in the Republic of Korea (2016-2021) In order to monitor the contamination of parasites (eggs) in children's play facilities, we investigated 11,429 soil samples from daycare centers, kindergartens, elementary schools, and parks across the country from January 2016 to December 2021. The national average rate was 8.7%, and the regions, which had higher parasites (eggs) positive rates than the average, were Jeollabuk-do (16.1%), Jeollanam-do (15.2%), Gwangju (12.3%), Busan (10.9%), Sejong (10.1%), and Gyeongsangnam-do (10.1%). Among the parasities (eggs) subject to investigation, the detection rates of Toxocara spp. by year ranged from 0.06 ~ 0.22% as follows: 1 case (0.22%) out of 472 in 2016, 2 cases (0.09%) out of 2,448 in 2017, 1 case (0.06%) out of 1,670 in 2018, 9 cases (0.39%) out of 2,348 in 2019, 4 cases (0.17%) out of 2,407 in 2020, and 1 case (0.16%) out of 2,084 in 2021. In particular, higher detection rates were observed in Seoul (0.63%), Jeju Island (0.50%), Gyeongsangnam-do (0.46%), Gwangju and Busan (0.35%), Gyeongsangbuk-do (0.24%), and Sejong (0.16%). As for the facilities, playgrounds of apartments (12.4%) showed the highest prevalence, followed by daycare centers (11.5%), parks (9.6%), kindergartens (8.7%), local playgrounds (8.1%), and elementary schools (6.5%). Among these, Toxocara spp. eggs were detected in daycare centers (0.37%), kindergartens (0.13%), elementary schools (0.2%), apartments (0.09%), and parks (0.14%). In addition, the older the completion date of construction, the higher the contamination rate with parasites was observed. In case of facilities managed with regular inspection cycle, playgrounds in parks (34.5%) showed the highest detection rate of recontamination, followed by daycare centers (25.2%), kindergartens (21.7%), elementary schools (20.5%), and apartments (20.4%). Additionally, children’s play facilities where Toxocara spp. eggs were re-detected included parks (1.17%) and elementary schools (0.2%). And Strongyloides spp. (2.16%), Ascaris spp. (1.7%), and Trichostrongylus spp. (0.4%) were most frequently found overall. Particularly, Toxocara spp. eggs were detected from play facilities nationwide at a rate of 0.16%. Consequently, there is an essential need for continuous monitoring of parasites contamination and regular education for preschool and school children to prevent soil-borne parasite infections. Keywords: Children’s play facilities, Monitoring of parasites contamination, Soil- borne parasite, Toxocara spp. eggs
학위논문(박사)--의생명과학과,2024. 2
Keywords: Children’s play facilities; Monitoring of parasites contamination; Soil-borne parasite; Toxocara spp. eggs